Two farnesyl pyrophosphate synthases, GhFPS1–2, in Gossypium hirsutum are involved in the biosynthesis of farnesol to attract parasitoid wasps - Hong ZHANG; Xin-zheng HUANG; Wei-xia JING; Dan-feng LIU; Khalid Hussain DHILOO; Zhi-min HAO; Yong-jun ZHANG (Journal of Integrative Agriculture, 2020)
Sesquiterpenoids play an import role in the direct or indirect defense of plants. Farnesyl pyrophosphate synthases (FPSs) catalyze the biosynthesis of farnesyl pyrophosphate, which is a key precursor of farnesol and (E)-β-farnesene. In the current study, two FPS genes in Gossypium hirsutum, GhFPS1 and GhFPS2, were heterologously cloned and functionally characterized in a greenhouse setting. The open reading frames for full-length GhFPS1 and GhFPS2 were each 1 029 nucleotides, and encoded two proteins of 342 amino acids with molecular weights of 39.4 kDa. The deduced amino acid sequences of GhFPS1–2 showed high identity to FPSs of other plants. Quantitative real-time PCR analysis revealed that GhFPS1 and GhFPS2 were highly expressed in G. hirsutum leaves, and were upregulated in methyl jasmonate (MeJA)-, methyl salicylate (MeSA)- and aphid infestation-treated cotton plants. The recombinant proteins of either GhFPS1 or GhFPS2 plus calf intestinal alkaline phosphatase could convert geranyl diphosphate (GPP) or isopentenyl diphosphate (IPP) to one major product, farnesol. Moreover, in electrophysiological response and Y-tube olfactometer assays, farnesol showed obvious attractiveness to female Aphidius gifuensis, which is an important parasitic wasp of aphids. Our findings suggest that two GhFPSs are involved in farnesol biosynthesis and they play a crucial role in indirect defense of cotton against aphid infestation.